Self- or Not-self is Malignant Tissues for the Host? - A. N. Shoutko (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
The aim of the chapter is to understand the number of theoretical inconsistencies that do not fit the idea of host immune defense against spontaneous cancer. They are: non-selective cytotoxic therapy of cancer is effective, acting harmfully for a host; legal deep lymphocytopenia, i.e., immunosuppression follows conventional cytotoxic therapy; high risk of new malignancies follows it too; malignant cells prefer to spread through lymph nodes, a favorite check-posts of immunity; accepted anti-angiogenic treatment restricts access of immunocytes inside a tumor. Considering the development of a tumor and its vessels, gradual exhaustion of hematopoietic stem cell number in blood and arising of cancer cachexia, a ratio of infectious morbidity and cancer mortality in their interrelation, extracted from experimental, clinical data and population statistics, we concluded, that mentioned and other discrepancies become regularities if the cells’ renewing in both malignant and normal tissues is a result of the recently discovered morphogenesis activity of circulating mononuclear cells, originating from the bone marrow and presenting by tissue’s committed stem cells and some subsets of morpho-angiogenic lymphocytes.